2014
DOI: 10.1175/jas-d-14-0018.1
|View full text |Cite
|
Sign up to set email alerts
|

Departures from Axisymmetric Balance Dynamics during Secondary Eyewall Formation

Abstract: Departures from axisymmetric balance dynamics are quantified during a case of secondary eyewall formation. The case occurred in a three-dimensional mesoscale convection-permitting numerical simulation of a tropical cyclone, integrated from an initial weak mesoscale vortex in an idealized quiescent environment. The simulation exhibits a canonical eyewall replacement cycle. Departures from balance dynamics are quantified by comparing the azimuthally averaged secondary circulation and corresponding tangential win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 76 publications
1
26
1
Order By: Relevance
“…Consistent with Figs. This stands in contrast to several recent studies that have concluded that the boundary layer winds in tropical cyclones are spun up by friction Abarca andMontgomery 2013, 2014). 16 shows that the spinup of the tangential wind field is at most heights due almost entirely to diabatic heating.…”
Section: What Drives Contraction?contrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with Figs. This stands in contrast to several recent studies that have concluded that the boundary layer winds in tropical cyclones are spun up by friction Abarca andMontgomery 2013, 2014). 16 shows that the spinup of the tangential wind field is at most heights due almost entirely to diabatic heating.…”
Section: What Drives Contraction?contrasting
confidence: 99%
“…Several recent papers (e.g., Smith et al 2009;Abarca andMontgomery 2013, 2014), have proposed that the spinup of the inner core of tropical cyclones is largely a result of frictionally driven inflow in the boundary layer as opposed to spinup occurring through a deep layer of heating-induced inflow. These studies argue that the inflow that is induced by friction is large enough such that the associated radial momentum advection outweighs the direct negative (spin down) effect of friction.…”
Section: April 2015mentioning
confidence: 99%
“…Recent studies on eyewall replacement cycles (ERCs) greatly advanced our understanding of this unique inner‐core structural change often occurring in intense tropical cyclones (TCs) [e.g., Houze et al ., ; Wu et al ., ; Rozoff et al ., ; Judt and Chen , ; Moon and Nolan , ; Fang and Zhang , ; Huang et al ., ; Abarca and Montgomery , , ; Kepert , ; Qiu and Tan , ; Wang et al ., ; Menelaou et al ., , ; Zhu and Zhu , , , hereafter ZZ14 and ZZ15]. Yet a timely accurate forecast of ERCs remains a challenge for numerical weather prediction.…”
Section: Introductionmentioning
confidence: 99%
“…This theory suggests that the surface friction increases the inflow underneath the broadened swirling wind at the top of the BL, and the strong inflow promotes the local development of supergradient winds in the SEF region. The other mechanism is based on the balanced feedback of the diabatic heating (Abarca & Montgomery, 2014;Rozoff et al, 2012;Zhu & Zhu, 2014). If sufficient diabatic heating occurs outside the primary eyewall, the secondary eyewall is induced by mass convergence at the low-level BL (Moon & Nolan, 2010;Zhu & Zhu, 2014).…”
Section: Introductionmentioning
confidence: 99%